SIKAP PEREMPUAN TERHADAP PEMUKULAN ISTRI (ANALISIS DATA SDKI 2007) - , RINA ISNAENI, S.SOS, Dr. Partini, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Intimate partner violence against women is present almost in all levels of society and can cause various injuries both physical and psychological. There are various policies of the government to reduce the occurrence of domestic violence, but the rate is still increasing from year to year. There are permissive attitudes in the society especially among women. It is seen from the results of IDHS 2007, when 30.8 percent of women stated their acceptance of wife beating for certain reasons. This study uses Indonesian Demographic And Health Survey data conducted in 2007. The purpose of this study was to statistically analyze factors associated with attitudes towards wife beating among womens in West Sumatra, South Sulawesi and Central Java. The data is processed with samples that meet criteria based on the difference in cultural and kinship background: married and ever married women in West Sumatra (n = 570), South Sulawesi (n = 1067), and in Central Java (n = 5383) that represent the matrilineal, patrilineal and parental kinship and culture. Chi-square (ÏÂ²) and logistic regression tests was used to analyze the data. The probability and correlation direction were observed from the odds ratio (OR) with confidence intervals (CI) of 95 percent (p-value â¤ 0.05). The result of multivariable analysis shows that there are no variables consistently associated with women's attitudes towards wife beating in this three provinces. Respondents occupation is significantly associated with attitudes toward wife beating only in West Sumatra, but there are no significant association in South Sulawesi and Central Java. Age and marital status have a significant association on women's attitudes towards wife beating in Central Java, while in West Sumatra and South Sulawesi are not. Access to mass media and decisionmaking has a significant association in opposite directions in South Sulawesi and Central Java. Respondentâs residence, education level and women's contribution on household expenditures have no association on women's attitudes towards wife beating in the three provinces. Patriarchal culture has an important role in influencing women's attitudes towards wife beating. Culture thatâs been constructed by the society and has been going since a long time ago have shaped womenâs attitudes related to violence. Beliefs and values of the culture unconsciously, fundamentally, deeply rooted, are learned and considered as a universal value that has been internalized by women, wife beating behavior for some reason is not perceived as an abuse.